Effect of Different Irrigation Periods and Mulching on Growth of Paulownia tomentosa (Thunb.) Steud. Seedlings. - Sherzad Omar Hamad (Zanco Journal of Pure and Applied Sciences, 2023)
To obtain high quality and quantity forest seedlings, silvicultural practices have been implemented in the nursery. Watering and mulching are two the most important silvicultural treatments that must be managed carefully in forest nursery in order to obtain healthy seedlings. The aim of the present study was to evaluate the effect of irrigation periods, mulching treatments and their interactions on the growth and development of Paulownia tomentosa seedlings. A factorial completely randomized design (CRD) with two factors was applied. The first factor was four irrigation periods which were once daily (D1), once every two days (D2), once every three days (D3), and once every four days (D4). The second factor was two mulching treatments which were mulching (M1) and non-mulching (M2). Each treatment was replicated five times. Morphological and physiological parameters of identified seedlings were studied. It is found that the irrigation periods significantly effect on the studied parameters, where the highest value of stem height increment (45.5 cm), stem diameter increment (4.74 cm), leaf number increment (10.3), stem dry weight (28.78 g), leaf dry weight (18.21 g), root dry weight (63.04 g), total dry weight (110.01 g), stem mass ratio (0.27), Dickson quality index (1.84), leaf area (3656.78 cm2) and specific leaf area (200.18 cm2 g-1) were recorded from the seedlings that watered daily(D1), while the lowest value of these parameters were obtained from the seedlings that watered once every four days(D4). Moreover, most of the biomass and physiological parameters were significantly affected by mulching treatments and the maximum value of them were found in the seedlings that mulched with hay. Thus, the study suggested that to enhance growth and development of Paulownia seedlings, the seedlings should be watered daily and mulched with an organic material.